(untitled) (Eurasian Research Bulletin, 2022)
It was found in the experiments that the leaf surface of the Sultan cotton cultivar grown in the conditions of weak, moderately saline and non-saline soils of Andijan region increases with the increase in soil salinity, the leaf plate becomes smaller, and the leaf thickens. In addition, it was studied in the experiment that the concentration of leaf aphid is lower than that of the non-salinity area, and the concentration of aphids before watering the cotton plant is higher depending on the average salinity